Budżet obywatelski – chęć zwiększenia partycypacji społecznej w rozwoju miast czy narzędzie marketingu politycznego w rękach prezydentów i burmistrzów? - Janicka, Roksana; Jędrowiak, Patryk (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2017)
The participation budget is nowadays more and more popular due to a democratic deficit on the level of local administration. People all over the world and (as stated in this article) also in Poland want to become a part of decision making process. They need to be heard. Because of that many mayors decide to implement in their cities the participation budget. Some of them want to give the people a tool that allows them to take a part of responsibility for city development. Others try to improve their public image thanks to the popularity of the participation budget and use this in the future for their reelection run.